Mobile Ecological Momentary Assessment of Postconcussion Symptoms and Recovery Outcomes. Issue 6 (November 2019) - Sufrinko, Alicia M.; Howie, Erin K.; Charek, Daniel B.; Elbin, R. J.; Collins, Michael W.; Kontos, Anthony P.
Abstract : Objective: Evaluate mobile ecological momentary assessment (mEMA) as an approach to measure sport-related concussion (SRC) symptoms, explore the relationships between clinical outcomes and mEMA, and determine whether mEMA was advantageous for predicting recovery outcomes compared to traditional symptom report. Setting: Outpatient concussion clinic. Participants: 20 athletes aged 12 to 19 years with SRC. Methods: Prospective study of mEMA surveys assessing activity and symptoms delivered via mobile application (3 time blocks daily) and clinical assessment at visit 1 (<72 hours postinjury) and visit 2 (6-18 days postinjury). Linear mixed models examined changes in mEMA symptoms over time and relationships among simultaneous report of activity type (cognitive, physical, sedentary, vestibular) and symptoms. Linear regressions evaluated the association among symptoms for activity types and clinical outcomes. Main Measures: mEMA symptom scores, Post-Concussion Symptom Scale, neurocognitive testing, vestibular/oculomotor screening (VOMS). Results: mEMA response rate was 52.4% ( N = 1155) for prompts and 50.4% per participant. Symptoms were lower in the morning ( P < .001) compared with afternoon and evening. Higher mEMA symptoms were reported during vestibular compared with physical ( P = .035) and sedentary ( P = .001) activities. mEMA symptoms were positively associated with Post-Concussion Symptom Scale (PCSS) ( P = .007), VOMS ( P = 0.001-0.002), and recovery time ( P < .001), but not neurocognitive scores. mEMA symptom score ( P = .021) was a better predictor of recovery time than PCSS at either clinic visit. Conclusion: mEMA overcomes barriers of traditional symptom scales by eliminating retrospective bias and capturing fluctuations in symptoms by time of day and activity type, ultimately helping clinicians refine symptom management strategies. Abstract : Supplemental Digital Content is Available in the Text.